Kedudukan Perempuan dalam Upacara Adat Perkawinan Orang Tolaki di Desa Mendikonu Kecamatan Amonggedo Kabupaten Konawe - Mey Dinasari; Erens Elvianus Koodoh (JURNAL KABANTI: Kerabat Antropologi, 2024)
This study explores the role of women in the Tolaki traditional marriage ceremony and the perspectives of men and women on this role. The research adopts a qualitative descriptive method and draws on socialist feminism theory. The findings reveal that women play a crucial role in various stages of the marriage customs. For instance, during the Mondutudu or proposal stage, the mother of the male/female side accompanies the family during the proposal. After the proposal, the bride-to-be is guided by a Tono Motuo or Female Traditional Leader, often the grandmother, who provides valuable advice for the future household. Additionally, women play a central role during the engagement ceremony, as they arrange for the treat of sekapur sirih Kalo Sara. The male party presents this treat through the Pabitara, which is then received by the woman. These customs highlight the important role women have in the Tolaki traditional marriage ceremony.